IMPACTS OF GLOBAL AND LOCAL COVID-19 CASES ON EMERGING STOCK MARKETS - Mustafa Emir Yücel; Özlem Fikirli; Hasan Şahin (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In this study, we examine the both local and global Covid-19 deaths and confirmed cases impact on stock markets return. We use the daily data from 26 countries, which are classified as emerging financial markets. According to the findings, a decrease in emerging stock market returns is not only due to local confirmed cases, but also from global confirmed cases. Our analysis also suggests that while an increase in total confirmed cases within the local variables leads to more decrease, total deaths within the global variables cause more decline in returns. When we consider the change in the stock market returns brought about by both local and global level confirmed cases rates and death rates increase, all global level variables (new confirmed cases, total confirmed deaths, new confirmed cases) except total confirmed cases lead to more decline. In other words, even if the countries control the covid-19 locally, the negative global impact on the stock market will continue.